Peran Kepolisian Resor Binjai Dalam Pelaksanaan Restorative Justice Terhadap Tindak Pidana Penganiayaan Anak - Robby Yusuf Syahputra; Rahmayanti; Sahlepi, Muhammad Arif (Legal Standing : Jurnal Ilmu Hukum, 2025)
Indonesia as a country based on law based on Article 1 paragraph (3) of the 1945 Constitution provides special protection for children in conflict with the law. In this context, the Binjai Police Resort (Polres) has a strategic role in implementing Restorative Justice through different mechanisms as regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This study aims to analyze: (1) the application of Restorative Justice to juvenile criminal offenses at the Binjai Police Resort; (2) obstacles encountered in its implementation; and (3) the role of the Binjai Police Resort in realizing the goal of diversion. The research method used is empirical juridical with a qualitative approach. Data were obtained through document studies, direct observation, and in-depth interviews with the PPA investigation unit, victims, perpetrators, and community leaders. Data analysis was conducted descriptively-qualitatively with an emphasis on the effectiveness of the application of the law in practice. The results of the study show that the success rate of diversion at the Binjai Police is quite high, namely 72.7% in 2023 and 73.3% in 2024, although it decreased to 60% in 2025. Factors inhibiting the implementation of Restorative Justice include decreasing public understanding, resistance from victims, economic limitations of perpetrators, minimal child-friendly facilities, efforts to have certified human resources, monitoring, and suboptimal involvement.